IMPROVING STUDENTS’ SKILL TO WRITE ISLAMIC HISTORICAL TEXTS THROUGH DICSTOM TECHNIQUE, THE TRIAL WEB SHIFT DESIGN, AND ENGAGEMENT STRATEGY AT STAI BUMI SILAMPARI LUBUKLINGGAU - Joni Helandri (El-Ghiroh : Jurnal Studi Keislaman, 2017)
This study aims to find the ability of third semester students, Prodi PAI (Islamic Religious Education) in writing texts of Islamic history in English. Students are taught 3 ways to write; (1) Dicstom, (2) Web Shift Trial, (3) Engagement, and (4) without technique. This research uses Quasi-experimental design method, and one-way ANOVA. The results showed that there is a difference between the students' ability in writing Islamic history text in English using the 3 ways mentioned above.